A Pre-Post Survey Analysis on Pharmacy Students' Perceptions of Pharmacist Roles in the Pharmaceutical Industry - Adina, Anugerah Budipratama; Yuwanda, Alhara; Budiastuti, Rizky Farmasita; Nopratilova, Nopratilova; Yusuf, Eddy; Tan, Suk Fei; Mawazi, Saeid Mezail; Herli, Amelia (Borneo Journal of Pharmacy, 2024)
The pharmaceutical industry is undergoing rapid evolution, characterized by a complex regulatory landscape and the need for diverse skill sets. This study aimed to assess pharmacy students’ perceptions of the pharmaceutical industry and the impact of a dedicated seminar on their career aspirations and knowledge. A pre-post online survey was administered to 55 undergraduate pharmacy students at the National Pharmacy Seminar 2024, hosted by Jakarta Global University. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test (p ≤0.05). Results indicate a strong preference for careers in state-owned pharmaceutical companies (63.6%) and research and development departments (34%). The seminar significantly enhanced participants’ understanding of pharmacists’ roles, industry complexities, drug development challenges, and regulatory requirements. Notably, 93% of participants reported that the seminar met their expectations and provided valuable insights for future career exploration. These findings underscore the importance of educational interventions in shaping pharmacy students’ career trajectories and aligning their knowledge with the dynamic pharmaceutical industry.